Reversible Tau Phosphorylation Induced by Synthetic Torpor in the Spinal Cord of the Rat - Timna Hitrec; Fabio Squarcio; Matteo Cerri; Davide Martelli; Alessandra Occhinegro; Emiliana Piscitiello; Domenico Tupone; Domenico Tupone; Roberto Amici; Marco Luppi (Frontiers Media S.A., 2021)
Tau is a key protein in neurons, where it affects the dynamics of the microtubule system. The hyperphosphorylation of Tau (PP-Tau) commonly leads to the formation of neurofibrillary tangles, as it occurs in tauopathies, a group of neurodegenerative diseases, including Alzheimer's. Hypothermia-related accumulation of PP-Tau has been described in hibernators and during synthetic torpor (ST), a torpor-like condition that has been induced in rats, a non-hibernating species. Remarkably, in ST PP-Tau is reversible and Tau de-phosphorylates within a few hours following the torpor bout, apparently not evolving into pathology. These observations have been limited to the brain, but in animal models of tauopathies, PP-Tau accumulation also appears to occur in the spinal cord (SpCo). The aim of the present work was to assess whether ST leads to PP-Tau accumulation in the SpCo and whether this process is reversible. Immunofluorescence (IF) for AT8 (to assess PP-Tau) and Tau-1 (non-phosphorylated Tau) was carried out on SpCo coronal sections. AT8-IF was clearly expressed in the dorsal horns (DH) during ST, while in the ventral horns (VH) no staining was observed. The AT8-IF completely disappeared after 6 h from the return to euthermia. Tau-1-IF disappeared in both DH and VH during ST, returning to normal levels during recovery. To shed light on the cellular process underlying the PP-Tau pattern observed, the inhibited form of the glycogen-synthase kinase 3β (the main kinase acting on Tau) was assessed using IF: VH (i.e., in motor neurons) were highly stained mainly during ST, while in DH there was no staining. Since tauopathies are also related to neuroinflammation, microglia activation was also assessed through morphometric analyses, but no ST-induced microglia activation was found in the SpCo. Taken together, the present results show that, in the DH of SpCo, ST induces a reversible accumulation of PP-Tau. Since during ST there is no motor activity, the lack of AT8-IF in VH may result from an activity-related process at a cellular level. Thus, ST demonstrates a newly-described physiological mechanism that is able to resolve the accumulation of PP-Tau and apparently avoid the neurodegenerative outcome.